Digital infrastructures of African Elections. Biometrics, voting machines and the democracyindustries in Kenya and Senegal - (:unkn) unknown (My University, 2025)
Digital infrastructures of African Elections. Biometrics, voting machines and the democracy industries in Kenya and SenegalVoting machines have become prominent features of public life in Africa. Parliamentary majorities advocate their use to support modernization policies, while opposition parties accuse them of hacking election databases to favor a « computer-generated » president. Citizens, now well-versed in voting technology, are demanding that servers be opened to reveal the truth about election results. They criticize the selection of technology providers and question whether operators respect their digital privacy and sovereignty. In Kenya, Senegal, and other countries across the continent, the election of the head of state unfolds within the context of a unique technical democracy -largely uncharted by Science and Technology Studies (STS) -characterized by the integration of computing technology debates within parliamentary democracy. What does the proliferation of digital tools, professions, and industries tell us about political authority, its relationship with technical authority, and the exercise of power in the postcolony? At the intersection of STS, African Studies, and the sociology of voting, this dissertation examines the close relationship between postcolonial practices of democracy and the development of digital and biometric industries. Far from being the product of administration evolution, digital voting developed alongside the expansion of citizenship and electoral practices after the 1960s Independence, through market creation and the industrial valorization of postcolonial popular participation. The thesis draws on a comparative investigation conducted from 2017 to 2022 on the digitization of voting in Kenya and Senegal. It is based on: a) Two ethnographic field studies during the presidential elections of 2017 (Kenya) and 2019 (Senegal), observing the articulation between public political debates (the stage, the interface)
Keywords: African Research